PENERAPAN MODEL COMPLETE SENTENCE DENGAN MEDIA GAMBAR SERI DALAM PENINGKATAN KETERAMPILAN MENULIS KARANGAN PADA SISWA KELAS III SD - MARIYANA, SHINTA (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Complete Sentence Model Using Picture Series Media in Improving Essay Writing Skills for the Third Grade Students of Elementary Schools. The objectives of this research is to improve essay writing skills. This research is a collaborative Classroom Action Research (CAR). Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed using quantitative and qualitative descriptive analysis consisting of data reduction, data display, and drawing conclusion or verification. The results of this research showed that: (1) the steps of the application of Complete Sentence using picture series media, namely: (a) the teacher explains learning competence, (b) the teacher explains the materials using picture series media, (c) the teacher divides the groups, (d) the teacher distributes students? worksheet, (e) the teacher explains students? worksheet, (f) the teacher gives assignments in group, (g) the teacher guides discussion and presentations, (h) the teacher and students draw conclusion and conduct reflection; (2) the application of Complete Sentence using picture series media can improve students? learning outcomes. The conclusion of this research is the application of Complete Sentence using picture series media can improve students? essay writing skills.Keywords: complete sentence, picture series media, essay writing Abstrak: Penerapan Model Complete Sentence dengan Media Gambar Seri  dalam Peningkatan Keterampilan Menulis Karangan pada Siswa Kelas III SD. Tujuan penelitian ini adalah meningkatkan keterampilan menulis karangan. Penelitian ini menggunakan penelitian tindakan kelas kolaboratif. Validasi data menggunakan triangulasi sumber dan teknik. Analisis data melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: (1) penerapan langkah-langkah model Complete Sentence dengan media gambar seri dilakukan sebagai berikut: (a) guru menyampaikan kompetensi yang akan dicapai, (b) guru menjelaskan materi menggunakan media gambar seri, (c) guru membentuk kelompok secara heterogen, (d) guru memberikan LKS, (e) guru menyajikan LKS, (f) guru memberikan tugas kelompok, (g) guru memandu diskusi dan presentasi kelompok, (h) guru bersama siswa membuat kesimpulan dan memberikan refleksi; (2) penerapan model Complete Sentence dengan media gambar seri dapat meningkatkan hasil belajar siswa. Kesimpulan penelitian ini adalah penerapan model Complete Sentence dengan media gambar seri dapat meningkatkan keterampilan menulis karangan.Kata kunci: complete sentence, media gambar seri, menulis karangan